The role of the study of the level of thyroglobulin in the washout fuid of the needle aspiration for the detection of cervical lymph node metastases in well-differentiated thyroid cancer - E. Kh. Gogieva; I. S. Romanov; E. E. Stanyakina; S. N. Berdnikov; E. L. Pimenova; A. I. Umarova (Сибирский онкологический журнал)
The study objective: to assess the diagnostic value of measuring the concentration of thyroglobulin (Tg) in the washout fluid of the fine needle aspiration (FNA) for the detection of well-differentiated thyroid cancer regional metastases.Material and Methods. The study included 64 patients with well-differentiated thyroid cancer. Ultrasound examination revealed 71 enlarged regional lymph nodes. The patients underwent simultaneous FNA cytology examination of lymph nodes and the study of Tg concentration in the washout fluid of the needle aspiration. Regional lymph node metastases were verified in 38 patients. These patients underwent surgery. Histological examination of surgical specimens was performed in 43 out of 71 cases.Results. The sensitivity, specificity, and accuracy of the FNA biopsy and the study of the concentration of thyroglobulin in the in the washout fluid of FNA were 88.5 %, 56.3 %, 76.2 % and 100 %, respectively. The rate of false-positive results of thyroid FNA biopsy was 16 %. The optimal cutoff value for FNA-Tg measurement was 4 g/ml. This made it possible to increase the sensitivity and specificity of the method to 100 %. It was found that the presence of circulating antibodies to Tg in the blood serum had no effect on the diagnostic value of FNA-Tg measurement (p=0.421). There were no statistically significant differences in the levels of thyroglobulin in the in the washout fluid of FNA between patients with Tg concentration above and below the cutoff values (3.9 [0.47; 39.9] ng/ ml vs 12.3 [0.57; 294.8] ng/ml).